TATA LETAK GUDANG RAW MATERIAL CHEMICAL MENGGUNAKAN METODE SHARED STORAGE DAN REL SPACE - Indramawan Hadi Kuswoyo; Atikha Sidhi Cahyana (Spektrum Industri, 2016)
Storage system in the manufacturing industry in this modern era is a very important role especially international scale company, may not directly produce or distribute all of the work unit. this led to the need for raw materials warehouse, warehouse storage systems should not be large in size because if supported by a good inventory of the warehouse to the maximum utilization of the problems faced by the company occurred in the warehouse of raw materials (raw materials). deficiencies in the arrangement of items in the warehouse procedures cause problems in the warehouse, so the warehouse impressed narrow and less structured cause inefficiencies time retrieval and storage of materials, as well as complicate the operator in handling the placement process raw materials. In the method of shared storage and rail space (relationchip chart) for the relationship between activity is indicated by activity relationship approach, which shows each activity as a single activity model in the form of a diagram. ARD basic idea of the link between patterns of flow of goods and location of service activities related to production activities. ARD is the development of ARC (activity relationship chart).Keywords : Warehouse shared storage, rel space